Gender differences in the relationship between obsessive-compulsive symptoms and suicide risk among psychiatric outpatient adolescents: the role of depressive symptoms, anxiety symptoms, and sleep disturbances - Fang, Xinwei; Qian, Xiulian; Hu, Xinzhu; Jiang, Huilan; Hu, Weiming (Frontiers in Public Health, 2025)
BackgroundSuicide has become one of the leading causes of death among adolescents, with an increased risk observed in the psychiatric outpatient population. Therefore, exploring its risk factors is crucial. Obsessive-compulsive symptoms, being common in this patient group, warrant investigation into their impact mechanisms on suicide risk.MethodsThis study enrolled 526 outpatient adolescents [396 females (75.29%); Mage = 15.39, SD = 1.23] who completed relevant questionnaires and provided demographic data during their clinic visit.ResultsObsessive-compulsive symptoms positively predicted suicide risk in both males and females, with depressive symptoms mediating this effect. Sleep disturbances played a mediating role only in females, while anxiety symptoms did not mediate the relationship in either gender.ConclusionClinicians should pay closer attention to adolescents presenting with obsessive-compulsive and depressive symptoms, as well as female adolescents with sleep disturbances, to mitigate their elevated suicide risk.